Melanocortin overexpression limits diet-induced inflammation and atherosclerosis in LDLR-/- mice - Nuutinen S; Ailanen L; Savontaus E; Rinne P (BIOSCIENTIFICA LTD, 2022)
Atherosclerosis is a chronic inflammatory disease of the arteries. The disease is initiated by endothelial dysfunction that allows the transport of leukocytes and low-density lipoprotein into the vessel wall forming atherosclerotic plaques. The melanocortin system is an endogenous peptide system that regulates, for example, energy homeostasis and cardiovascular function. Melanocortin treatment with endogenous or synthetic melanocortin peptides reduces body weight, protects the endothelium and alleviates vascular inflammation, but the long-term effects of melanocortin system activation on atheroprogression remain largely unknown. In this study, we evaluated the effects of transgenic melanocortin overexpression in a mouse model of atherosclerosis. Low-density lipoprotein receptor-deficient mice overexpressing alpha- and gamma(3)-MSH (MSH-OE) and their wild-type littermates were fed either a regular chow or Western-style diet for 16 weeks. During this time, their metabolic parameters were monitored. The aortae were collected for functional analysis, and the plaques in the aortic root and arch were characterised by histological and immunohistochemical stainings. The aortic expression of inflammatory mediators was determined by quantitative PCR. We found that transgenic MSH-OE improved glucose tolerance and limited atherosclerotic plaque formation particularly in Western diet-fed mice. In terms of aortic vasoreactivity, MSH-OE blunted alpha1-adrenoceptor-mediated vasoconstriction and enhanced relaxation response to acetylcholine, indicating improved endothelial function. In addition, MSH-OE markedly attenuated Western diet-induced upregulation of proinflammatory cytokines (Ccl2, Ccl5 and Il6) that contribute to the pathogenesis of atherosclerosis. These results show that the activation of the melanocortin system improves glucose homeostasis and limits diet-induced vascular inflammation and atherosclerotic plaque formation.